(untitled) - Daniels, John D. (Upper Saddle River, NJ., 2004)
This classic bestseller discusses the differences faced in international environments, the overall strategies companies can take, and practical alternatives for operating abroad. Its abundance of colorful maps, strong engaging and opening cases, and classic and contemporary examples provide a balanced approach to all functions of business. More than 15 new cases have been added to this edition, all of which engage the reader with hot topical issues; these include Cran Chik, Luikoil, Cisco Systems, Johnson & Johnson, and Global Sofware Piracy. It has excellent coverage of Latin America, and reviews the latest institutional actions, market trends, and company activities. It provides an extensive background section, a comparative environmental frameworks section, a section on theories and institutions (trade and investment), a section on the world financial environment, business-government relationships, operations and tactical alternatives, and a section on managing business internationally. For readers involved in international business, whether they are employees, managers, or owners/CEOs of such corporations. Also an excellent resource for individuals seeking to expand their current businesses to the international market.
Keywords: International business enterprises,International economic relations,Investments, Foreign